2021
DOI: 10.1080/19406940.2021.1915848
|View full text |Cite
|
Sign up to set email alerts
|

Discursive resistance to gender diversity in sport governance: sport as a unique field?

Abstract: Although diversity is an often cited organisational value, its support is often muted when it pertains to boards of governance. The aim of this study is to identify discursive practices that may prevent or limit the implementation of measures to increase gender balance in sport governance at the national and international levels. Drawing on a total of 60 qualitative, semi-structured interviews with board members, we explore both the content of and reasons for discursive opposition to implementing gender balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 41 publications
0
29
0
4
Order By: Relevance
“…Previous research has shown that, when recruiting new members to sports boards, only certain types of people possessing certain traits are seen as what Claringbould and Knoppers (2007) conceptualize a proper 'fit'. The perceived proper fit consists of gendered and socially constructed ideas of qualifications, skills, traits, knowledge, characteristics, and needs, which are often not based on systematic identification of the board's needs, but rather on the ways the present board members (i.e., men) have qualified themselves for board membership (Adriaanse and Schofield 2014;Claringbould and Knoppers 2007;Hovden 2000Hovden , 2010Knoppers et al 2021). However, sports boards' selection and recruitment processes are assumed to be gender neutral and of good quality, which removes a gender balance as an objective in these processes (Claringbould and Knoppers 2007;Sotiriadou and De Haan 2019).…”
Section: Recruitment and The Right Fitmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous research has shown that, when recruiting new members to sports boards, only certain types of people possessing certain traits are seen as what Claringbould and Knoppers (2007) conceptualize a proper 'fit'. The perceived proper fit consists of gendered and socially constructed ideas of qualifications, skills, traits, knowledge, characteristics, and needs, which are often not based on systematic identification of the board's needs, but rather on the ways the present board members (i.e., men) have qualified themselves for board membership (Adriaanse and Schofield 2014;Claringbould and Knoppers 2007;Hovden 2000Hovden , 2010Knoppers et al 2021). However, sports boards' selection and recruitment processes are assumed to be gender neutral and of good quality, which removes a gender balance as an objective in these processes (Claringbould and Knoppers 2007;Sotiriadou and De Haan 2019).…”
Section: Recruitment and The Right Fitmentioning
confidence: 99%
“…Because only individuals (women and men) who fit this profile are included in male networks and selected as candidates for leadership positions, the board's existing values are guaranteed and reproduced, which leads to the board staying homogenous (Hovden 2000(Hovden , 2010Sotiriadou et al 2017). Men as the majority can frame the recruitment and selection processes of the board members, and thus maintain the male-dominated culture, into which their own habitus better fits (Knoppers et al 2021;Piggott et al 2019). Women aiming for board membership then tend to distance themselves from their gender and prove their 'fit' in order to be seen as possible candidates (Claringbould and Knoppers 2007;cf.…”
Section: Recruitment and The Right Fitmentioning
confidence: 99%
See 3 more Smart Citations